Tubular Structures XIV - Gardner, Leroy (CRC Press, 2012)
A pertinent reference source for architects, civil and mechanical engineers, designers, steel fabricators and contractors, manufacturers of hollow sections or related construction products, trade associations involved with tubing, owners or developers of tubular structures, steel specification committees, academics and research students all around the world.